(untitled) - A E Cawkell (London, 1993)
This book provides an invaluable guide to the terminology of information technology and systems, filling the need for an up-to-date reference tool that is both clear and easy to use, and yet gives fully detailed explanations for each entry. The book offers comprehensive and detailed definitions around 5.000 terms, an easy-to-use reference, and a guide for the information industry
Keywords: computers - dictionaries,information technology - dictionaries